Mitochondrial energetic metabolism—some general principles. Issue 3 (25th February 2013) - Mazat, Jean‐Pierre; Ransac, Stéphane; Heiske, Margit; Devin, Anne; Rigoulet, Michel
Abstract Summary In nonphotosynthetic organisms, mitochondria are the power plant of the cell, emphasizing their great potentiality for adenosine triphosphate (ATP) synthesis from the redox span between nutrients and oxygen. Also of great importance is their role in the maintenance of the cell redox balance. Even though crystallographic structures of respiratory complexes, ATP synthase, and ATP/adenosine diphosphate (ADP) carrier are now quite well known, the coupling between ATP synthesis and cell redox state remains a controversial issue. In this review, we will present some of the processes that allow a modular coupling between ATP synthesis and redox state. Furthermore, we will present some theoretical approaches of this highly integrated system. © 2013 IUBMB Life, 65(3):171–179, 2013